Joyce The Return of the Repressed - Friedman, Susan Stanford (Cornell University Press, 1993)
Did James Joyce, that icon of modernity, spearhead the dismantling of the Cartesian subject? Or was he a supreme example of a modern man forever divided and never fully known to himself? This volume reads the dialogue of contradictory cultural voices in Joyce's works-revolutionary and reactionary, critical and subject to critique, marginal and central. It includes ten essays that identify repressed elements in Joyce's writings and examine how psychic and cultural repressions persistently surface in his texts. Contributors include Joseph A. Boone, Marilyn L. Brownstein, Jay Clayton, Laura Doyle, Susan Stanford Friedman, Christine Froula, Ellen Carol Jones, Alberto Moreirias, Richard Pearce, and Robert Spoo.